SEMINARIO DE INVESTIGACION EN TRANSFORMADA RÁPIDA DE FOURIER - Castro Chadid, Iván; Departamento de Matemáticas, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
A rigorous deduction of sorne of the m a in properties ofthe product ofKronecker for matrices is presented.